Auxin and cytokinin control fate determination of cotyledons in the one-leaf plant Monophyllaea glabra - Kinoshita, Ayaka; Tsukaya, Hirokazu (Frontiers in Plant Science, 2022)
One-leaf plants in the Gesneriaceae family initially have two cotyledons of identical size; one cotyledon stops growing shortly after germination, whereas the other continues indeterminate growth. Factors involved in the unequal growth have been investigated, and a competitive relationship between the two cotyledons was previously proposed. However, questions regarding the fate determination of the two cotyledons remain: Why does only one cotyledon grow indeterminately while the other stops; is the fate of the cotyledons reversible; and what role does light quality play in the fate determination of the cotyledons? In this study, physiological experiments using the one-leaf plant species Monophyllaea glabra suggest that a biased auxin concentration between the two cotyledons and subsequent cytokinin levels may determine the fate of the cotyledons. In addition, observation of relatively mature individuals without hormone treatment and younger individuals with cytokinin treatment under laboratory growth conditions revealed that the fate determination of the microcotyledon is reversible. Although light quality has been suggested to be important for the determination of cotyledon fate in Streptocarpus rexii, an anisocotylous species, we conclude that light quality is not important in M. glabra.